Dreams and delights - Beck, L. Adams (Lily Adams), 1862-1931 (Salt Lake City, UT : Project Gutenberg, 2023)
"Dreams and Delights" by L. Adams Beck is a collection of short stories written in the early 20th century. This literary work transports readers across diverse landscapes, exploring themes of longing, spirituality, and the human experience as envisioned through the delicate interplay of dreams and reality. The preface hints at a mystical exploration of the feminine spirit and connection to the divine, suggesting that the narratives will delve into the hearts and minds of women influenced by transcendent forces. The opening of the collection introduces us to Beatrice Veronica Law Leslie, who adopts the pen name "V. Lydiat" to carve out her identity in the literary world. Torn between her unfulfilled desires for adventure and creativity, she ultimately seeks solace in writing while forging a mysterious connection with a shadowy figure who inspires her work. Through dream sequences and vivid imagery, the story hints at deeper layers of consciousness and the quest for self-discovery, as Beatrice navigates her path from a life constrained by societal expectations to one rich with purpose and passion for artistic expression. This intriguing premise sets the stage for the enchanting stories that follow, captivating readers with its layers of meaning and poetic reflections. (This is an automatically generated summary.)
"V. Lydiat" -- The sea of lilies -- The bride of a god -- The beloved of the gods -- The hidden one -- The marriage of the princess -- The wisdom of the Orient -- Stately Julia -- The Island of Pearls -- The wonderful pilgrimage to Amarnath -- The man without a sword.
Release date is 2023-01-14
Al Haines, Cindy Beyer & the online Distributed Proofreaders Canada team at https://www.pgdpcanada.net
Keywords: Short stories; Asia -- Fiction; Orient -- Fiction